Trends and insights into glymphatic system research and Alzheimer’s disease: a bibliometric analysis from 2014 to 2023 - L. Olegário, Raphael; Lilian L. Martini, Luciana; C. Teixeira, Priscila; Diego de C. Bispo, Diógenes; von Glehn, Felipe; T. Nóbrega, Otávio; Francisco Camargo, Einstein (Brazilian Journal of Health and Biomedical Sciences, 2025)
Introduction: Over the past decade, research on the glymphatic system has garnered increasing attention within the scientific community. This system, initially explored through animal models and magnetic resonance imaging tracer-based studies, holds potential implications for understanding neurodegenerative diseases, notably Alzheimer’s disease. However, a bibliometric analysis of research related to the glymphatic system and Alzheimer’s disease is lacking. Objective: Our study aimed to conduct a comprehensive analysis of the existing literature on glymphatic system research, with a particular focus on its intersection with studies of the pathology of Alzheimer’s disease. By synthesizing available data, we sought to identify trends, gaps and potential avenues for future research and collaboration in this evolving field. Methods and resources: We utilized statistical techniques to analyze data obtained from the Web of Science Core Collection database. Our methodology encompassed various aspects, including frequency of publication, geographical distribution, citation networks, and thematic analysis of authors’ keywords. Results and discussion: Our analysis covered a wide range of publications spanning the last decade and revealed a gradual increase in research output over time. Notably, we observed a significant level of international collaboration, underscoring the global nature of scientific inquiry in this domain. However, disparities in research capacity and collaboration were apparent, particularly among regions with limited resources. Conclusion: Our findings highlight the importance of continued interdisciplinary collaboration and exploration to advance our understanding the function of the glymphatic system and its relevance to neurodegenerative disorders. Addressing disparities in research capacity and fostering global collaboration are essential steps toward developing effective interventions for Alzheimer's disease and related conditions.